Danger at the haunted gate - Wiley, Jesse (Boston : Houghton Mifflin Harcourt, 2018)
It's 1850, and you are continuing on the treacherous Oregon Trail. In this second book of four, you need to get to Devil's Gate, the halfway mark on your 2,000-mile journey West. Keep watch! Danger awaits you on your way to those eerie cliffs. Which path will you choose in the face of danger? With more than twenty possible endings, choose wrong and you'll never make it to Devil's Gate. Choose right and blaze a trail that gets you closer to Oregon City!
6.3
3-6
780L
Keywords: Oregon National Historic Trail -- History -- Juvenile fiction; Overland journeys to the Pacific -- Juvenile fiction; Frontier and pioneer life -- Juvenile fiction; Adventure stories; Plot-your-own stories; Oregon National Historic Trail -- History -- Fiction; Overland journeys to the Pacific -- Fiction; Frontier and pioneer life -- Fiction; Adventure and adventurers -- Fiction; Plot-your-own stories; Historical fiction; Action and adventure fiction; Choose-your-own stories; Oregon Trail -- Fiction